THE COMPREHENSION OF SOCIAL MEDIA ETHICS BY RINA HASANAH VOCATIONAL SCHOOL STUDENTS - M. Dissha Najiah Al Yas’a; Achmad Hufad; Siti Komariah (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
Currently, social media cannot be separated from the lives of Indonesian people due to the needs and developmental characteristics of its generation. Apart from that, social media is also very useful in improving people’s social and economic capabilities where they can gain income and wider knowledge. However, the massive use of social media has not been matched by an understanding of its ethics. This article was written with the aim of revealing how social media ethics are understood by Rina Hasanah Vocational School students. Through this research, it is hoped that it can contribute to overcoming social media ethical issues because understanding is an important component in forming behavior. The method used in this study is a qualitative approach with descriptive methods. These approaches and methods were chosen in order to be able to describe and describe the actual general state of students’ understanding and experience regarding ethics in social media. Data collection techniques used in this study were interviews, observation, and documentation studies. Meanwhile, the data analysis techniques used are reduction, data presentation, and drawing conclusions/verifying data. The rese’rch results show that the understanding of social media ethics at Rina Hasanah Vocational School can be said to be sufficient, but still needs to be improved where students rarely think about the ethics of an action before behaving on social media. They understand that social media must take positive and beneficial actions. However, they have not been able to understand and think about the impact if they take unethical actions on social media.